ONE-YEAR TREATMENT OUTCOMES WITH SUBCUTANEOUS SEMAGLUTIDE AT HOSPITAL QUEEN ELIZABETH II:: A RETROSPECTIVE ANALYSIS - Cheong, Yee Weai; Tee, Hwee Ching; Ho, Jin Hui; Lim, Jing Li (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Glucagon-like Peptide-1 receptor agonists (GLP-1 RAs) mimic endogenous GLP-1, improving glycemic control and promoting weight loss. Nevertheless, there is limited data available on the effect of semaglutide use among type 2 diabetes (T2D) patients undergoing insulin therapy, particularly those with high insulin requirements. METHODOLOGY We aimed to investigate the effects of the addition of subcutaneous semaglutide to a standard regimen of insulin on T2D patients, focusing on changes in HbA1c levels, body weight and total daily dose (TDD) of insulin. In this retrospective chart review, T2D patients who received once-weekly subcutaneous semaglutide with insulin were recruited from the Endocrine Unit of the Hospital Queen Elizabeth II (HQE II) from 2021 to 2023. Follow-up assessments occurred at 3-6 months and 9-12 months postinitiation, with the recording of key parameters such as HbA1c, weight, insulin TDD and adverse events. RESULT Our study recruited a total of 35 patients and found that there were significant improvements across all parameters. HbA1c levels decreased from a mean of 8.9% at baseline to 7.7% at 9-12 months, representing a reduction of 1.2% (p <0.001). Weight decreased from a mean of 92.0 kg at baseline to 84.2 kg at 9-12 months, with a mean reduction of 7.7 kg (-8.4%) (95%CI: 4.9-10.6, p <0.001). Insulin TDD decreased from a median of 72u (40 - 114) at baseline to 48u (24 - 80) at 9-12 months (p <0.001). Six individuals experienced gastrointestinal side effects, with one discontinuing due to intolerable diarrhea. In the subgroup with insulin resistance, there were profound reductions in TDD of insulin used without compromising glycemic control. CONCLUSION The study confirmed the efficacy of once-weekly semaglutide in managing T2DM patients on insulin therapy, including those on basal-bolus and pre-mixed regimens. Further research is recommended to assess its effects on patients with high insulin requirements.